Navigating the Politics of Remembering - Meihana P (UTS ePRESS)
Remembering the past is not as straight forward as it might appear. The histories that we choose to retell and privilege speak to contemporary concerns. For Rangitāne, Ngāti Kuia and Ngāti Apa, the indigenous peoples of the northern South Island of Aotearoa New Zealand, history is political. Histories are recounted in the present for a purpose, that is, to maintain the mana (prestige, authority, influence) of the community to whom the histories belong. This article touches on some recent examples of history speaking in the present.
Keywords: Rangitāne; Ngāti Kuia; Ngāti Apa; Tupaia; Tuia 250; Te Rangikāheke; 2102 Curatorial and Related Studies; 2103 Historical Studies